(untitled) (Geologica Macedonica, 2019)
The latest mineralogical study of the Borov Dor copper porphyry deposit have selected a total of 6 representative samples from 4 exploration drill holes and treated in laboratory conditions with a study under optical polarization microscope and a scanning electron microscope (SEM). Six representative pairs of monomineral and polymineral parageneses were identified and their chemical compositions with their associated minerals were determined, too. Quartz-chalcopyrite-sulfide paragenesis stands out as dominant and mainly chalcopyrites are very close their theoretical compositions. Within simple sulphide paragenesis come quartz-pyrite-chalcopyrite in which pyrite is dominant with compositions that are also close to theoretical. Chalcopyrite-bornite paragenesis stands out as transformation one during the decay of the solid solution, where the lattice structure of the bornite in the corroded chalcopyrite predominates. The compositions show a tendency of transition in both chalcopyrite and bornite directions and defectivness is observed. In a similar constellation are the solid solution decays in the chalcopyrite-cubanite pair where the compositions of both interaction minerals have undergone modification, but clearly indicate the transformation phase. Even more characteristic is the transformation phase in chalcopyrite-bornite-idaite where the transitions are gradual and the mixed phases defective to allowable level. This sequence of transformations ended with the tetrahedra-tenantite phases with multiple variants. Of particular note is the quartz-molybdenite phase with pure molybdenite rod-like forms as a representative of higher temperature mineral paragenesis. Key words: ore minerals; mineral association; porphyry copper deposit; scanning electron microscope